2012
DOI: 10.1126/scisignal.2002437
|View full text |Cite
|
Sign up to set email alerts
|

The lin-4 MicroRNA Targets the LIN-14 Transcription Factor to Inhibit Netrin-Mediated Axon Attraction

Abstract: lin-4 (miR-125) microRNAs are deeply conserved across animal phylogeny. They are among the first microRNAs discovered and were implicated in regulating developmental timing in C. elegans. In this study, we report that mutations in lin-4 microRNA specifically suppress the AVM axon guidance defects in slt-1 mutants through enhancement of netrin attraction. lin-4 expression in AVM neurons rescued lin-4 mutant phenotypes in AVM axon guidance, suggesting that lin-4 acts cell autonomously in AVM to inhibit its axon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 35 publications
0
74
0
1
Order By: Relevance
“…AVM axon regeneration in lin-4 mutants is not significantly different from that in wild-type animals (fig. S5A), suggesting that different developmental timing microRNAs play different roles in AVM: lin-4 is used to time AVM axon connectivity as reported previously (14); let-7 is used to time developmental decline in AVM axon regeneration.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…AVM axon regeneration in lin-4 mutants is not significantly different from that in wild-type animals (fig. S5A), suggesting that different developmental timing microRNAs play different roles in AVM: lin-4 is used to time AVM axon connectivity as reported previously (14); let-7 is used to time developmental decline in AVM axon regeneration.…”
mentioning
confidence: 70%
“…MicroRNA expression is either spatially restricted or temporally regulated in neuronal development (11-14). To explore the role of microRNAs in neuronal regeneration, we examined AVM axon regeneration in mutants defective in microRNA biogenesis, dcr-1 and alg-1 (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a fish model of axonal growth, the knockdown of miR-204 leads to misguided growth of retinal ganglion cell axons into retinal layers; downregulation of miR-204, which targets ephrin type receptor B 2 (Ephb2) and ephrin B3 (Efnb3), both of which are important signaling molecules in axon guidance, rescues these defects (Conte et al, 2014). In C. elegans, the miR-125a/b homolog lin-4 reduces axonal growth induced by the axon guidance factor UNC-6 (a Netrin homolog) via inhibition of the transcription factor LIN-14 (Zou et al, 2012). In contrast, it has been shown that increased LIN-14 activity induces axonal initiation in C. elegans HSN neurons independently of external guiding cues (e.g.…”
Section: Neuronal Polarization Axon Pathfinding and Dendritogenesismentioning
confidence: 99%
“…While most miRNAs downregulate gene expression, there are examples of miRNA-mediated upregulation of target gene expression during cell cycle arrest, suggesting that miRNA function is complex and context dependent (Vasudevan et al, 2007; Orom et al, 2008). miRNAs have been implicated in many aspects of development and disease including cell cycle, cell differentiation, apoptosis, life span, developmental timing, stress responses, neural development and regeneration, cancers, and neurodegenerative disorders (Boehm and Slack, 2005; Bushati and Cohen, 2007; Chang et al, 2009; Ambros, 2011; Sayed and Abdellatif, 2011; Zhang et al, 2011; Boulias and Horvitz, 2012; Cochella and Hobert, 2012a; Saito and Saito, 2012; Zou et al, 2012, 2013). …”
Section: Introductionmentioning
confidence: 99%